PURUSA DAN PRADANA SEBAGAI KONSEP KESETARAAN GENDER DALAM AGAMA HINDU - Warta, I Nyoman (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2024)
The equality of Purusa and Pradana in its essence is to maintain the health of the universe and its contents. With their respective duties and functions, harmony is created. Likewise, the equality of men and women is created differently but in essence is the same. The understanding of gender or equality has become an important subject in various aspects of human life, including in the context of religion and spirituality. In Hinduism, the concept of gender is not only limited to biological differences between men and women, but also includes social structures, cultural norms, and expanded spiritual roles. Equality in the Hindu perspective reflects the complexity of human life, which is reflected in sacred texts, religious rituals, and daily practices. Gender issues in Hinduism have far-reaching implications in the understanding of gender roles in society and spiritual life. The concept not only encompasses the relationship between men and women in the context of family and society, but also involves the role of gods and goddesses who reflect different principles in the universe. Thus, the understanding of gender in Hinduism provides a rich view of the dynamics of human relationships with humans, humans with other life and humans with God (Brahman). The understanding of these positions contradicts the depiction of gender in Hinduism. Men are portrayed as protectors and women as providers of prosperity who are worshipped in the form of deities, and are even portrayed as transcending gender understanding in the exploration of social roles and sexuality. Thus, there is no aspect that distinguishes the position of men and women, both in their duties and responsibilities as human beings. The main difference between women and men is limited to biological differences, so the concept of gender is entirely a socio-cultural concept that applies in certain societies according to their nature or karmic purposes.